CLINICAL AUDIT ON PRE-OPERATIVE FASTING OF ELECTIVE SURGICAL PATIENTS AT AYUB TEACHING HOSPITAL ABBOTTABAD. - Ali Mujtaba; Muhammad Raza; Hamid Nasim; Faizan Taj; Adil Muhammad; Muhammad Attique Ur Rehman (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
A preoperative fast is required before anesthesia. Preoperative fasting is primarily done to lower stomach volume and acidity, which lowers the risk of pulmonary aspiration. At Ayub Teaching Hospital, patients occasionally fasted for extended periods of time, despite the numerous negative effects of prolonged fasting. To assess the preoperative fasting duration by patients who were scheduled for elective surgery in Ayub Teaching Hospital Abbottabad, from May 27 to June 27, 2024, a cross-sectional study was carried out, and all 70 patients who were under general anesthesia were included in the interviews that were done 24 hours after surgery. The majority of patients, 77.1%, fasted for more than 10 hours before their procedures for solid food. A significant majority of the patients, 72.9%, fasted for more than 10 hours for liquid. These figures show that most of the patients fasted more than the recommended time for both solid and liquid. A small fraction, 6.7%, felt hungry after fasting for solid food. More than half of the patients, 69.5% felt thirst after prolong fasting for liquid. In conclusion, this audit has illuminated significant noncompliance with established preoperative fasting practices, with a predominant number of patients fasting for durations well beyond recommendations. By addressing these systemic shortcomings through policy updates, comprehensive staff training, and operational enhancements, healthcare institutions can markedly improve patient outcomes and ensure alignment with international standards of care.